Kharif tomato cultivation for doubling farmers’ income in plateau ecosystems - Nath, Sujit K; Mishra, C; Swastika, S (Indian Farming, 2020)
Tomato is the second most important vegetable of the world after potato. Though it is popularly known as a winter crop in India, it can be cultivated in the well drained soils of plateau ecosystems in kharif season. Tribal farmers of Deogarh district, coming under North-western plateau agro-climatic zone of Odisha, with the scientific know-how of local Krishi Vigyan Kendra are able to produce kharif tomato in about hundred acres. The production was market oriented and helped to increase their income satisfactorily.